Preliminary study of Huai Qi Huang granules delay the development of primary glomerular diseases in human. (October 2014) - Duan, Shao-Bin; Pan, Peng; Xu, Qian; Li, Xiejia; Liu, Na; Xu, Jun
Abstract Objective: To evaluate the effects of Huai Qi Huang (HQH) granules on primary glomerulonephritis patients, and to discuss its possible mechanisms. Method: Sixteen patients diagnosed with primary glomerular disease between December 2011 and December 2012 were enrolled. Their blood and urine samples were collected at day 0 (the baseline levels), 30, and 90 of receiving HQH granules orally. Levels of creatinine and cystatin C (Cys-C) in serum and urine, and total protein and albumin in urine were measured by automatic biochemical analyzer. Neutrophil gelatinase-associated lipocalin (NGAL) in serum and urine was tested by ELISA; serum malondialdehyde (MDA) was measured by thiobarbituric acid method, the erythrocyte count in urine was calculated under light microscope. Results: Serum levels of creatinine, MDA, Cys-C and NGAL at day 30 and 90 were significantly lower than the baseline levels. Urinary levels of Cys-C, NGAL, total protein, albumin and erythrocyte counts were also decreased; level of estimated glomerular filtration (eGFR) was increased. Conclusion: HQH granules have certain effect on delaying the development of primary glomerular disease with mild proteinuria and hematuresis in patients. This study may supply a new treatment for primary glomerular diseases.